Curriculum change in English language curriculum advocates higher order thinking skills and standards-based assessments in Malaysian primary schools - Sulaiman, Tajularipin; Mohd Ayub, Ahmad Fauzi; Sulaiman, Suriati (MCSER Publishing, 2015)
Malaysia undertook a comprehensive reform of the primary education by introducing KSSR or the Primary School Standards-Based Curriculum in 2011. The curriculum change has largely driven by the setting of national standards for KSSR subjects. Accordingly, the Standards-Based English Language Curriculum (SBELC) was designed with significant changes in curriculum documents and organization. SBELC not only demands changes in teacher knowledge, attitudes, and instructional practices but also seeks teachers to design such activities and assessments that require pupils to comprehend the language input and answer questions with high levels of cognitive skills that emphasize on conceptual understanding and integration of many language skills and language focus rather than traditional rote learning skills. The purpose of this paper is to review curriculum change in the new English language curriculum in which higher order thinking skills and standards-based assessments are given due attention in Malaysian primary schools.